Influence of Nutripro-Aqua Incorporated Feed on Water Quality, Primary Pond Productivity and Growth in the Culture of Pearl Spot - V., Jayaprakas; Abraham, Kurian Mathew (Fishery Technology, 2025)
Supplementary feeding may influence the water quality parameters, especially the productivity. Productivity is one of the principal water quality parameters that determine fish production. An experiment was carried out to evaluate the relationship between productivity and growth in Etroplus suratensis fed diet containing Nutripro-Aqua, a commercial growth promoter. Fishes were cultured in cement tanks for 180 days and the growth and productivity were monitored periodically. Nutripro-Aqua was administered through a standard pelletized feed with 40% protein at four dosages, 0, 8, 9.5 and 11%. Productivity and growth of fishes were found to be significantly high in 11% treatment, which indicates the influence of the pond productivity on growth of fishes.